A method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified non-woven fabric

By loading silver nanoparticles in situ on the nonwoven fabric and using the skeleton structure formed by tannic acid and ferric chloride, the problem of uneven distribution of silver nanoparticles in the traditional method is solved, and the separation and catalytic function of ultrafiltration membrane is combined to achieve efficient removal of multi-component pollutants.

CN114797498BActive Publication Date: 2025-03-11NANJING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210629425.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-04
Publication Date
2025-03-11
Estimated Expiration
2042-06-04

AI Technical Summary

Technical Problem

Traditional methods easily lead to agglomeration when loading silver nanoparticles on the support, resulting in uneven distribution, making it difficult to achieve effective separation and catalytic functions.

Method used

By using tanninic acid and ferric chloride as the intermediate coating, it is in contact with the silver ion solution, and the silver nanoparticles are loaded in situ to modify the non-woven fabric to achieve the combination of separation and catalytic functions.

Benefits of technology

The uniform distribution of silver nanoparticles on the non-woven fabric is achieved, the separation performance of the ultrafiltration membrane is enhanced, and catalytic capacity is imparted, which can efficiently remove multi-component pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003677979120000011
    Figure HDA0003677979120000011
  • Figure HDA0003677979120000012
    Figure HDA0003677979120000012
  • Figure HDA0003677979120000021
    Figure HDA0003677979120000021
Patent Text Reader

Abstract

The invention discloses a method for preparing a multifunctional ultrafiltration membrane based on a non-woven fabric modified with silver nanoparticles. The method is to prepare a multifunctional ultrafiltration membrane using a non-solvent induced phase separation method with a non-woven fabric modified with silver nanoparticles as a substrate. Specifically, after the non-woven fabric is treated with ferric chloride and tannic acid solution, a tannic acid-iron skeleton is formed on it, and then it is placed in a silver nitrate solution, and the surface is in situ loaded with uniformly distributed and equal-sized silver nanoparticles. An ultrafiltration membrane casting liquid is prepared, and a multifunctional ultrafiltration membrane with a separation-catalysis spatial order is prepared with the modified non-woven fabric as a substrate. The silver loading imparts a catalytic function to the molecular sieve membrane, which not only maintains the original high flux and high retention of the ultrafiltration membrane, but also realizes efficient catalytic removal of pollutants. Based on the orderly arrangement of ultrafiltration and catalysis, the separation function of the membrane removes pollutants that have a negative impact on subsequent catalysis in advance, and realizes efficient and synchronous removal of multi-component pollutants in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified non-woven fabric, and belongs to the technical field of environmental functional material preparation. Background Art

[0002] With the rapid economic development and the continuous growth of population, the demand for water resources is increasing. Freshwater resource pollution is becoming increasingly serious, and available freshwater resources are decreasing. Based on this, my country has proposed the resource utilization of sewage as a fundamental way to solve the shortage of water resources. In the process of industrial wastewater reuse and treatment, organic pollutants have attracted great attention due to their environmental toxicity, and the development of advanced technologies to treat organic pollutants has become a hot issue. Among many advanced technologies, the excellent catalytic performance and simple reaction mechanism of metal nanoparticles make them unique in the process of wastewater reuse. However, there are often multi-component pollutants in wastewater, with complex occurrence forms and mutual influence between components, which makes the catalytic performance of metal materials easily affected. Therefore, membrane methods are often used to pre-remove pollutants in multi-component pollutants that have a negative impact on the catalytic process. The synergistic coupling of catalytic process and membrane technology is a hot technology for achieving efficient and synchronous removal of complex micropollutants.

[0003] The traditional sodium borohydride chemical reduction method first needs to be complexed with free silver ions on the substrate, and then contacted with a reducing agent, which will cause the silver nanoparticles loaded on the substrate to agglomerate, resulting in uneven distribution of silver nanoparticles. The method of loading silver nanoparticles in the present invention is superior to the traditional additive blending loading method, and the selected tannic acid and ferric chloride are both cheap and safe drugs. Tannic acid, as a typical natural polyphenol, has strong reducibility and reduces silver ions to silver nanoparticles at room temperature without adding additional conditions. In addition, since tannic acid has an aromatic structure, its inherent adhesive properties enable it to form a coating on various non-porous or porous substrates by itself, avoiding the shedding of nanomaterials. Based on this, tannic acid and trivalent iron ions are coordinated through organic-inorganic hybridization to form a tannic acid-iron skeleton as an intermediate coating, and after contacting with a silver ion solution, the silver nanoparticles evenly distributed on the in-situ loading are achieved to achieve the purpose of modifying non-woven fabrics and modifying membrane substrates. The combination of separation and catalytic functions in the process of wastewater resource utilization by membrane technology is realized. Summary of the invention

[0004] The invention relates to a method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified non-woven fabric.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] The invention discloses a method for preparing a multifunctional ultrafiltration membrane based on non-woven fabric modified with silver nanoparticles. The modified non-woven fabric is used as a substrate, and a layer of ultrafiltration membrane with separation performance is prepared on the upper layer.

[0007] This is accomplished by:

[0008] Step 1: prepare ferric chloride, tannic acid and silver nitrate solutions respectively;

[0009] Step 2: soaking the non-woven fabric in a ferric chloride solution, then soaking it in a tannic acid solution, then washing it with deionized water to remove unreacted residues, and air-drying it naturally;

[0010] Step 3: Place the nonwoven fabric in the above step 2 in a silver nitrate solution, soak it for a period of time in dark conditions, wash away the unreacted residue with deionized water, and place it to dry naturally;

[0011] Step 4: Prepare a casting solution, prepare an ultrafiltration membrane on the non-woven fabric in step 3 by a non-solvent induced phase separation method, and place it in deionized water for later use.

[0012] In the above step 4, the modified non-woven fabric is used as the substrate, and an ultrafiltration membrane with separation performance is prepared on the upper layer thereof.

[0013] In the above step 1, the concentration of the ferric chloride solution is 0.584-2.336 g / L, the concentration of the tannic acid solution is 2.042-8.166 g / L, and the concentration of the silver nitrate solution is 1.73-6.92 g / L.

[0014] In the above step 1, the molar ratio of tannic acid to ferric chloride is 1:1-1:6.

[0015] In the above step 3, the non-woven fabric is immersed in the silver nitrate solution for more than 5 hours.

[0016] In the above step 4, the main components of the prepared casting solution are polyethersulfone (PES): 15-18%, polyethylene glycol (PEG20000): 6-10%, and N,N-dimethylformamide (DMF): 72-79%.

[0017] The scraping film thickness in the above step 4 can be selected to be 50-500 μm.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] (1) The preparation process is simple to operate, the raw materials are easily available and pollution-free, and can be industrially produced;

[0020] (2) The modified nonwoven fabric can be used as the substrate of the ultrafiltration membrane, adding catalytic properties to the ultrafiltration membrane, and obtaining a multifunctional ultrafiltration membrane with spatially ordered separation catalysis, thereby realizing the combination of separation-catalysis functions. Based on the orderly arrangement of ultrafiltration and catalysis, the separation function of the membrane will pre-remove macromolecular pollutants that have a negative impact on the subsequent catalytic process, and simultaneously improve the pollutant removal performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are the front and back views of the multifunctional ultrafiltration membrane prepared in Example 1 of the present invention.

[0022] Figure 2 The multifunctional ultrafiltration membrane prepared in Example 1 of the present invention includes: (a) a low-magnification cross-sectional SEM image, (b) a high-magnification SEM image of the PES membrane separation layer, and (c) a membrane surface SEM image.

[0023] Figure 3 These are the following pictures of the non-woven fabric modified with silver nanoparticles in Example 1 of the present invention: (a) SEM picture at low magnification, (b) SEM picture at medium magnification, and (c) SEM picture at high magnification.

[0024] Figure 4 (a) low-magnification SEM image and (b) high-magnification SEM image of the silver nanoparticle-modified non-woven fabric in Example 2 of the present invention.

[0025] Figure 5 This is a high-magnification SEM image of the non-woven fabric modified with silver nanoparticles in Comparative Example 1 of the present invention.

[0026] Figure 6 These are the following: (a) low-magnification SEM image and (b) high-magnification SEM image of the non-woven fabric modified with silver nanoparticles in Comparative Example 2 of the present invention.

[0027] Figure 7 This is a high-magnification SEM image of the non-woven fabric modified with silver nanoparticles in Comparative Example 3 of the present invention.

[0028] Figure 8 In Example 1 of the present invention: (a) XRD patterns of non-woven fabric modified with silver nanoparticles and unmodified non-woven fabric; (b) thermogravimetric analysis of non-woven fabric modified with silver nanoparticles, TA-Fe modified non-woven fabric and unmodified non-woven fabric; (c) removal effect of methylene blue (MB) by membrane (M1) with unmodified non-woven fabric as substrate, membrane (M2) with silver nanoparticle modified non-woven fabric as substrate, silver nanoparticle modified non-woven fabric and unmodified non-woven fabric in Example 1; (d) removal effect of multi-component pollutants by M2. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with embodiments

[0030] The present invention imparts catalytic properties to the ultrafiltration membrane by in-situ loading of silver nanoparticles on the membrane substrate, thereby obtaining a separation-catalysis multifunctional ultrafiltration membrane with spatial order. Based on the orderly arrangement of ultrafiltration and catalysis, a variety of pollutants in water can be removed excellently.

[0031] Embodiment 1:

[0032] Step 1: Prepare 500 mL each of 2.336 g / L ferric chloride solution, 8.166 g / L tannic acid solution, and 6.92 g / L silver nitrate solution at room temperature.

[0033] Step 2:

[0034] Immerse a clean non-woven fabric of 8×8 cm in a ferric chloride solution at room temperature for 5 minutes until the non-woven fabric is completely soaked; take it out and soak it in a tannic acid solution for 5 minutes without rinsing; take out the non-woven fabric, wash it with deionized water to remove unreacted residues, and air-dry it naturally.

[0035] Step 3:

[0036] The nonwoven fabric in step 2 is placed in a silver nitrate solution and immersed in darkness for 24 hours to load silver nanoparticles in situ on the nonwoven fabric. Unreacted residues are washed off with deionized water and the nonwoven fabric is allowed to air dry naturally.

[0037] Step 4:

[0038] PES ultrafiltration membrane was prepared by phase inversion method. 31.14g of dried polyethersulfone resin (PES) and 15.09g of dried polyethylene glycol (PEG20000) were added to 150mL of NN dimethylformamide (DMF) solution. The mixture was stirred at 60°C for 8h until the solution was in a uniform, transparent polymer solution state, i.e., the casting solution. The prepared casting solution was allowed to stand for degassing at room temperature for 12h, and the casting solution was evenly coated on the silver nanoparticle-modified nonwoven fabric and the unmodified nonwoven fabric using an automatic scraper with a scraper thickness of 320μm. After staying in the air for 20s, the glass plate was immediately immersed in deionized water horizontally to induce phase inversion. After immersion for 15min, it was transferred to deionized water for overnight storage to ensure complete phase inversion and solvent elution. The membrane with the unmodified nonwoven fabric as the substrate was named M1, and the membrane with the silver nanoparticle-modified nonwoven fabric as the substrate was named M2.

[0039] This example is an application experiment. M1 and M2 prepared in Example 1 are installed in a filter device in a forward direction to conduct a dynamic catalytic experiment. The feed liquid is 1.5 mg / L methylene blue (MB) and 0.195 g / L sodium borohydride (NaBH 4 ) mixed solution, membrane effective area 12.56cm 2The permeate was collected and the MB concentration in the effluent was determined. In addition, a 1.5 mg / L MB, 5 mg / L humic acid (HA) and 0.195 g / L NaBH 4 The multi-component pollutant water sample represented by was passed through the membrane to study the effect of the newly prepared membrane on the simultaneous removal of multi-component pollutants. M2 was placed in reverse, with the non-woven fabric facing the influent, to study the contribution of the spatial order structure of the membrane to the dynamic catalytic process. MB and HA concentrations were determined using a UV spectrophotometer. All experiments were measured once, samples were collected and analyzed three times, and the results were averaged.

[0040] From the attached Figure 1 It can be seen that the front side of the prepared multifunctional membrane is white, and the non-woven fabric on the back side changes from white before treatment to yellow. Figure 2 It can be seen that an ultrafiltration membrane with a thickness of about 250μm was prepared by the phase inversion method. Figure a shows the porous asymmetric cross-sectional structure of the ultrafiltration membrane prepared with silver nanoparticle-modified non-woven fabric as the substrate, including a dense separation layer and a support layer with a finger-like pore structure. It can be clearly seen that the support layer and the non-woven fabric are tightly connected, and the dense separation layer and the porous support layer structure remain intact. It can be seen that the structure of the ultrafiltration membrane is not adversely affected by the modification of the substrate. Figure b shows the relatively smooth inner pore surface of the ultrafiltration membrane, with a clear finger-like pore structure, and the non-woven fabric matrix modified with silver nanoparticles does not damage the structure of the ultrafiltration membrane selection layer. Figure c shows that the pores on the surface of the ultrafiltration membrane are evenly distributed, and the pore size is mainly distributed in the range of 10-20nm. From the attached Figure 3 It can be seen that the silver nanoparticles are evenly distributed on the surface of the non-woven fabric, with a particle size of about 30nm, equal size, and a large number. In summary, M2 can load the ultrafiltration membrane onto the modified non-woven fabric very well.

[0041] The silver nanoparticle modified nonwoven fabric and the unmodified nonwoven fabric in Example 1 were subjected to X-ray diffraction analysis. The results are shown in the attached figure. Figure 8 As shown in Figure a, compared with the unmodified non-woven fabric, the silver nanoparticle-modified non-woven fabric has two diffraction peaks at 38.1° and 44.3°. According to the comparison with the JCPDS36-1451 card, it can be seen that they correspond to the (111) and (200) crystal planes of Ag, respectively, proving the presence of silver nanoparticles on the surface of the silver-modified non-woven fabric.

[0042] Thermogravimetric analysis was performed on the silver nanoparticle modified nonwoven fabric, TA-Fe modified nonwoven fabric and unmodified nonwoven fabric in Example 1. The results are shown in the attached figure. Figure 8 As shown in b, under air conditions, the residual weight of the unmodified non-woven fabric and the TA-Fe modified non-woven fabric was 0. After the introduction of silver nanoparticles, the residual weight increased. From the analysis of the final weight loss results, it can be seen that nearly 3.5% of the residual amount is the content of the loaded silver nanoparticles, indicating that the silver nanoparticles were successfully loaded onto the non-woven fabric.

[0043] Dynamic catalytic experiments were conducted on methylene blue (MB) using the membrane (M1) based on the unmodified nonwoven fabric in Example 1, the membrane (M2) based on the silver nanoparticle-modified nonwoven fabric, the silver nanoparticle-modified nonwoven fabric, and the unmodified nonwoven fabric. The experimental results are shown in the attached figure. Figure 8 As shown in c, the unmodified nonwoven fabric has almost no removal effect on MB; the silver nanoparticle-modified nonwoven fabric has little effect on MB removal due to the catalytic activity of silver nanoparticles. 4 , MB was reduced and the removal rate reached 90.2%; M1 had a certain removal of MB (17.8%), which was caused by the MB retention and adsorption removal caused by the ultrafiltration membrane; M2 had a removal rate of MB of 78.4%, which was caused by the ultrafiltration membrane covering a small amount of Ag nanoparticles, but it could still maintain excellent performance.

[0044] The filtration experiment of the membrane (M2) with silver nanoparticles modified nonwoven fabric as the substrate in Example 1 for removing multi-component pollutants was carried out. The results are shown in the attached figure. Figure 8 d. When removing MB alone, M2 showed excellent removal performance for MB, with a removal rate of more than 90%. In the system where HA coexists, the removal effect of M2 on MB was not affected and remained at a high level, with a removal rate of nearly 100% for HA. When the membrane was placed in reverse, so that the non-woven fabric layer with catalytic function faced the inlet side, its MB removal performance dropped sharply, and the removal efficiency was only 14.7%. This is due to the presence of HA, which competes for active reducing components and covers the silver surface, causing a sharp drop in active sites, which greatly negatively affects the process of catalytic reduction to remove MB, resulting in a decrease in MB removal rate. In the forward placement mode of the membrane, since the selective layer faces the inlet side, HA is trapped on the surface of the ultrafiltration membrane separation layer and cannot contact the catalytic layer at the bottom, achieving its pre-removal and gradient separation of pollutants, so that HA does not have a negative impact on the removal of MB by M2. Therefore, the multifunctional ultrafiltration membrane with silver-modified non-woven fabric as the carrier can achieve gradient and efficient removal of multi-component pollutants under low pressure.

[0045] Embodiment 2:

[0046] Step 1:

[0047] Prepare 500 mL of each of 2.336 g / L ferric chloride solution, 8.166 g / L tannic acid solution and 6.92 g / L silver nitrate solution at room temperature. Add the ferric chloride solution to the stirred tannic acid solution to prepare a tannic acid-iron solution.

[0048] Step 2:

[0049] Soak a clean non-woven fabric of 8×8 cm in the tannic acid-iron solution for 5 minutes at room temperature, take out the non-woven fabric, wash it with deionized water to remove unreacted residues, and air-dry it naturally.

[0050] Step 3:

[0051] The nonwoven fabric in step 2 is placed in a silver nitrate solution and immersed in darkness for 24 hours to load silver nanoparticles in situ on the nonwoven fabric. Unreacted residues are washed off with deionized water and the nonwoven fabric is allowed to air dry naturally.

[0052] Step 4:

[0053] Same as step 4 of Example 1.

[0054] Scanning electron microscopy revealed that Figure 4 As shown, silver nanoparticles are evenly distributed on the surface of the non-woven fabric, with a particle size of 20 to 30 nm, equal size, and a large number, but there are some other substances additionally attached to the surface of the non-woven fabric.

[0055] Comparative Example 1:

[0056] Step 1: Prepare 500 mL each of 2.336 g / L ferric chloride solution, 8.166 g / L tannic acid solution, and 6.92 g / L silver nitrate solution at room temperature.

[0057] Step 2:

[0058] At room temperature, 8×8 cm clean non-woven fabric was immersed in the ferric chloride solution for 5 minutes until the non-woven fabric was completely soaked; after rinsing the non-woven fabric with deionized water, it was immersed in the tannic acid solution for 5 minutes, the non-woven fabric was taken out and washed with deionized water to remove unreacted residues, and naturally air-dried.

[0059] Step 3:

[0060] The nonwoven fabric in step 2 is placed in a silver nitrate solution and immersed in darkness for 24 hours to load silver nanoparticles in situ on the nonwoven fabric. Unreacted residues are washed off with deionized water and the nonwoven fabric is allowed to air dry naturally.

[0061] Step 4:

[0062] Same as step 4 of Example 1.

[0063] Scanning electron microscopy revealed that Figure 5 As shown, when the ferric chloride solution on the surface of the non-woven fabric was rinsed, the amount of silver nanoparticles loaded thereon was significantly reduced.

[0064] Comparative Example 2:

[0065] Step 1:

[0066] Prepare 500 mL of each of 2.336 g / L ferric chloride solution, 8.166 g / L tannic acid solution and 6.92 g / L silver nitrate solution at room temperature. Add the ferric chloride solution to the stirred tannic acid solution to prepare a tannic acid-iron solution.

[0067] Step 2:

[0068] A clean non-woven fabric of 8×8 cm was immersed in the tannic acid-iron solution at room temperature for 15 minutes, the non-woven fabric was taken out and washed with deionized water to remove unreacted residues, and then naturally air-dried.

[0069] Step 3:

[0070] The nonwoven fabric in step 2 is placed in a silver nitrate solution and immersed in darkness for 24 hours to load silver nanoparticles in situ on the nonwoven fabric. Unreacted residues are washed off with deionized water and the nonwoven fabric is allowed to air dry naturally.

[0071] Step 4:

[0072] Same as step 4 of Example 1.

[0073] Scanning electron microscopy revealed that Figure 6 As shown, silver nanoparticles are densely distributed on the surface of the non-woven fabric, with a particle size of 30 to 40 nm, uniform in size, and relatively large in size. However, due to the long immersion time in the tannic acid iron solution, a large amount of tannic acid-iron is attached to the surface.

[0074] Comparative Example 3:

[0075] Step 1: Prepare 1 L of 1.168 g / L ferric chloride solution, 4.083 g / L tannic acid solution, and 3.46 g / L silver nitrate solution at room temperature.

[0076] Step 2:

[0077] Immerse a clean non-woven fabric of 8×8 cm in a ferric chloride solution at room temperature for 5 minutes until the non-woven fabric is completely soaked; rinse the non-woven fabric with deionized water, and then soak it in a tannic acid solution for 5 minutes. Take out the non-woven fabric, wash it with deionized water to remove unreacted residues, and air-dry it naturally.

[0078] Step 3:

[0079] The nonwoven fabric in step 2 is placed in a silver nitrate solution and immersed in darkness for 24 hours to load silver nanoparticles in situ on the nonwoven fabric. Unreacted residues are washed off with deionized water and the nonwoven fabric is allowed to air dry naturally.

[0080] Step 4:

[0081] Same as step 4 of Example 1.

[0082] Scanning electron microscopy revealed that Figure 7 As shown, it is found from Comparative Example 1 that when the solution concentration is halved, the loading amount of silver nanoparticles is significantly reduced.

Claims

1. A method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified non-woven fabric, characterized in that: The modified non-woven fabric is used as a substrate, and an ultrafiltration membrane with separation performance is prepared on the upper layer thereof, comprising the following steps: (1) Prepare ferric chloride, tannic acid and silver nitrate solutions respectively; (2) soaking the nonwoven fabric in a ferric chloride solution, then soaking it in a tannic acid solution, then washing it with deionized water to remove unreacted residues, and air-drying it naturally; (3) placing the nonwoven fabric in step 2 above in a silver nitrate solution, soaking it for a period of time in dark conditions, washing away unreacted residues with deionized water, and air-drying it naturally; (4) preparing a casting solution, preparing an ultrafiltration membrane on the non-woven fabric prepared in step 3 by a non-solvent induced phase separation method, and placing the membrane in deionized water for later use.

2. The method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified nonwoven fabric according to claim 1, characterized in that: In step 1, the concentration of the ferric chloride solution is 0.584-2.336 g / L, the concentration of the tannic acid solution is 2.042-8.166 g / L, and the concentration of the silver nitrate solution is 1.73-6.92 g / L.

3. The method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified nonwoven fabric according to claim 1, characterized in that: In step 1, the molar ratio of tannic acid to ferric chloride is 1:1 – 1:

6.

4. The method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified nonwoven fabric according to claim 1, characterized in that: In step 3, the non-woven fabric is immersed in the silver nitrate solution for more than 5 hours.

5. The method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified nonwoven fabric according to claim 1, characterized in that: In step 4, the composition of the prepared casting solution is polyethersulfone: 15-18%, polyethylene glycol: 6-10%, and N,N-dimethylformamide: 72-79%.

6. The method for preparing a multifunctional ultrafiltration membrane based on silver nanoparticle-modified nonwoven fabric according to claim 1, characterized in that: The film thickness is 50-500 µm.

Citation Information

Patent Citations

  • Preparation and application of support layer functionalized adsorption-enhanced type composite ultrafiltration membrane

    CN104492286A

  • Multifunctional foamed natural rubber with high catalytic performance and antibacterial performance and preparation method thereof

    CN110938230A